2014
DOI: 10.1590/s1517-83822014000400005
|View full text |Cite
|
Sign up to set email alerts
|

Microbial dynamics during azo dye degradation in a UASB reactor supplied with yeast extract

Abstract: The present work aimed to investigate the microbial dynamics during the anaerobic treatment of the azo dye blue HRFL in bench scale upflow anaerobic sludge bed (UASB) reactor operated at ambient temperature. Sludge samples were collected under distinct operational phases, when the reactor were stable (low variation of color removal), to assess the effect of glucose and yeast extract as source of carbon and redox mediators, respectively. Reactors performance was evaluated based on COD (chemical oxygen demand) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…e final MLVSS concentration was 2000 mg/L. e increase in the concentrations of MLSS and MLVSS throughout the operation may be attributed to the fact that microorganisms degrade dyes to organic material and water [26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…e final MLVSS concentration was 2000 mg/L. e increase in the concentrations of MLSS and MLVSS throughout the operation may be attributed to the fact that microorganisms degrade dyes to organic material and water [26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…The genera Desulfovibrio (0.39% and 17.8%), Pseudomonas (3.7% and 10.3%), Desulfobulbus (0.02% and 2.3%) and Dehalobacterium (0.13% 25%) were found with higher relative abundance in the biomass of the support material when compared to the bottom biomass of the ANSTBR reactor (respectively) (Table 2). The genus Pseudomonas plays an important role in the discoloration process of azo dyes under anaerobic conditions, and thus these microorganisms are versatile in the degradation of these compounds and can be tolerant to toxic byproducts such as aromatic amines 62–64 . Microorganisms related to the Pseudomonas genus are able to produce azoredutases that help in the degradation and discoloration of the dyes, as observed by microaerophilic and aerobic processes 65 .…”
Section: Resultsmentioning
confidence: 99%
“…Microorganisms related to the Pseudomonas genus are able to produce azoredutases that help in the degradation and discoloration of the dyes, as observed by microaerophilic and aerobic processes 65 . The presence of this microbial group is essential in terms of providing reductive equivalents for azo dye reduction and/or methane production when methanogenic archaea are present in the system 64 . Thus, the occurrence of this microbial group in the support material is justified owing to its great metabolic versatility in which there are supposedly higher concentrations of DB22 degradation byproducts and a large part of other compounds already have been converted at the bottom of the AnSTBR reactor.…”
Section: Resultsmentioning
confidence: 99%
“…In this manner, the addition of yeast extract provides macro and micronutrients easing the biological activity. Despite improving the anaerobic degradation of azo dyes, recent studies demonstrated that yeast extract addition to UASB reactor, at a concentration of 350mg/L, did not promote changes in the microbial structure [10].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the application of immobilized redox mediators in microbial fuel cells was tested for electricity generation with simultaneous azo dye removal due to facilitated electrons transfer from bacteria to anodes and azo dyes [8]. In this context, the use of low cost redox mediators have been suggested, such as commercial yeast extract (source of riboflavin) [2,9,10] or residual yeast from the brewing industry [11,12]. Dyes are deficient in carbon and nitrogen sources, and the biodegradation of dyes without any supplement of these sources may be hampered.…”
Section: Introductionmentioning
confidence: 99%